The level of political efficacy among senior citizens in selected barangays in Jaro, Leyte. - Celis, Annel Ruth, et al.; Nebrida, Leoniza Frances P. (Tacloban City Annel Ruth Celis, 2010)
Jaro is a fourth class municipality in the Province of Leyte. The researches were interested in finding out the degree to which senior citizens of the said municipality perceived their own level of political efficacy. Political efficacy which refers to the feeling that political and social change is possible and that the individual citizen can play a part in bringing about this change, is composed of internal and external political efficacy. Internal political efficacy is the confidence of the individual in his or her own abilities to understand politics and to act politically. External political efficacy is the individual's belief in the responsiveness of the political system.
This research was conducted in the municipality of Jaro, Leyte from January 22, 2010 until January 31, 2010. The respondents of this study were determined using systematic sampling with random start in a multi-stage sampling. They were composed of 195 senior citizens distributed among the five selected barangays- Barangay I, Barangay III, Barangay Macanip, Barangay Macopa and Barangay Canhandugan.
Data were presented, analyzed, and interpreted with the use of mean, point-biserial, Eta, and R-value. Results showed that the senior citizens perceived themselves as having an average level of political efficacy. The researchers identified that the socio-demographic variables have no significant relationship, and recruitment and mobilization with the level of political efficacy.
The findings of the study are important as they provide a good perspective in understanding the state of the political efficacy and will contribute to the existing body of literature on the topic. With a level of political efficacy among senior citizens we can explain better how senior citizens perceive the government to be responsiveness to their needs and welfare and the extent to which they can influence governmental decisions.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science